On the experience of the sublime in architectural atmospheres: a phenomenological inquiry - Kudahl, Benedikte (Frontiers in Psychology, 2025)
The concept of the sublime has inspired numerous philosophical inquiries throughout the evolution of aesthetic thought. This article examines the type of experience referenced by philosophers in their discussions surrounding the concept of the sublime. I thoroughly explore the experiential dimensions by analyzing the sublime from a psychological perspective anchored in phenomenology. More specifically, this research concentrates on the manner in which the sublime is perceived within architectural contexts. Through a phenomenological examination of architectural experiences depicted in esteemed literary works, I propose a comprehensive framework detailing the experiential manifestations of the sublime. Finally, I discuss the philosophical, aesthetic, and psychological implications of the sublime experience, as well as its intricate relationship with atmosphere.